2012
DOI: 10.1074/jbc.m111.291179
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-Transferase Omega 1 Activity Is Sufficient to Suppress Neurodegeneration in a Drosophila Model of Parkinson Disease

Abstract: Background: Glutathione S-transferase Omega has been shown to be associated with Parkinson disease.Results: Drosophila GSTO1 regulates mitochondrial ATP synthase activity in parkin mutants.Conclusion: Drosophila GSTO1 plays a protective role in a Drosophila model of Parkinson disease.Significance: These findings may lead to a better understanding of the molecular mechanism of neuroprotection due to GSTO in Parkinson disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 56 publications
0
73
2
Order By: Relevance
“…The GSTs in the present study appeared to show little or no peroxidase activity for the tested substrates either in this or a previous study ). This appears to be in contrast to the previous reports for these GST classes and demonstrates that GST isoforms from the same class may have quite different substrate specificity (Singh et al 2001;Burmeister et al 2008;Jaramillo-Gutierrez et al 2009;Piaggi et al 2010;Nair and Choi 2011;Kim et al 2012). …”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…The GSTs in the present study appeared to show little or no peroxidase activity for the tested substrates either in this or a previous study ). This appears to be in contrast to the previous reports for these GST classes and demonstrates that GST isoforms from the same class may have quite different substrate specificity (Singh et al 2001;Burmeister et al 2008;Jaramillo-Gutierrez et al 2009;Piaggi et al 2010;Nair and Choi 2011;Kim et al 2012). …”
Section: Discussioncontrasting
confidence: 91%
“…It was shown some of the modulation was dependent upon Omega enzyme thiol activity. Omega enzyme activity was also found to be important for glutathionylation of ATP synthase β subunit for activity of F 1 F 0 -ATP synthase activity (Kim et al 2012). These data show the Omega GSTs possess a substrate/protein interaction specificity extending beyond p38b kinase interactions, as well as each Omega GST showing unique preferences.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…[22][23][24] The third mutation was a mutation in CWF19L1 in an obligatory splice site (c.96411G.A, i.e., the first base of intron 9, always G, is changed to an A; figure 1D). Sanger sequencing confirmed this mutation in the affected siblings and demonstrated that it is absent in 200 Turkish individuals without neurologic disorder.…”
Section: Results Exome Sequencing Identifies Mutation Inmentioning
confidence: 99%
“…There is increasing evidence that GSTOs are involved in various biological and clinically significant settings, including drug resistance (Yin et al 2005), Alzheimer's disease (Li et al 2003), the action of anti-inflammatory drugs (Laliberte et al 2003), and susceptibility to chronic obstructive pulmonary disease (COPD) (Dulhunty et al 2001). By regulating mitochondrial ATP synthase activity, DmGSTO1 has been demonstrated to play a protective role in a Drosophila model of Parkinson's disease (Kim et al 2012). However, the role of GSTO in insect have not been fully investigated and should be further determined.…”
Section: Introductionmentioning
confidence: 99%